THE ESSENCE OF THE INSTITUTE OF SUSPENSION OF EXECUTION OF AN ADMINISTRATIVE ACT - Geghamyan, Elina (State and Law, 2022)
The right to judicial protection and one of the essential features of an administrative act, enforceability, inevitably collide at a particular moment in the judicial procedure of challenging the administrative acts. In this process, the institution of suspension of execution of an administrative act is aimed at ensuring an effective balance between the fundamental principle of the effectiveness of the law and the protection of the rights of the person challenging the administrative act. Yet, despite this circumstance, the essence of the institution of suspending the execution of an administrative act, both at the theoretical level and in law enforcement practice, still needs to be perceived equally.In this scientific article, in the context of the fundamental right to judicial protection and as a result of the discussion of the recommendations of the Council of Europe and constitutional regulations in the Republic of Armenia, the essence of the components of the concept of "suspension of execution of an administrative act" and the legal content of this institute are revealed. As a result, the author concludes that the suspension of execution of an administrative act can serve its primary purposes of the suppression of excessive damage to the plaintiff and the preservation of the situation existing at the time of applying to the court only if its legal interpretation ensures the preservation of the actual and legal situation existing at the time of applying to the court. Based on what is stated in the scientific article, the essence of the discussed institution is revealed, and its definition is given.
Keywords: suspension of execution of an administrative act; right to judicial protection; enforceability of an administrative act; effectiveness of the law; effectiveness of the protection of rights; execution of an administrative act; preliminary measures of judicial protection